2001
DOI: 10.1097/00005768-200102000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Fitness, fatness, and coronary heart disease risk in adolescents: the Northern Ireland Young Hearts Project

Abstract: . Purpose: The purpose of this study was to examine the independence and relative strengths of association between coronary heart disease (CHD) risk status and both body fatness and cardiorespiratory (C-R) fitness in 12-and 15-yr-old adolescents. Methods: The study cohort consisted of 1015 schoolchildren aged 12 and 15 yr (251 12-yr-old boys, 258 12-yr-old girls, 252 15-yr-old boys, and 254 15-yr-old girls), representing a 2% random sample of each population group. For each child, height, weight, sexual maturi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
77
3
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 32 publications
16
77
3
4
Order By: Relevance
“…In An outpatient program for obese children U Korsten-Reck et al addition, independent of age, they found higher HDL-C values in girls than in boys. The same trend was seen in Northern Ireland by Boreham et al, 23 who described a cohort of subjects between the ages 12 and 15 y. All these results are primarily explained by the influence of sex hormones in that age group.…”
Section: Discussionsupporting
confidence: 75%
“…In An outpatient program for obese children U Korsten-Reck et al addition, independent of age, they found higher HDL-C values in girls than in boys. The same trend was seen in Northern Ireland by Boreham et al, 23 who described a cohort of subjects between the ages 12 and 15 y. All these results are primarily explained by the influence of sex hormones in that age group.…”
Section: Discussionsupporting
confidence: 75%
“…In contrast, Boreham et al 18 found that the relationships between aerobic fitness and CVD risk factors were not statistically significant after adjustment for fatness but the relationships between fatness and CVD risk factors remained significant after adjustment for aerobic fitness. Using logistic regression, Nielsen and Andersen 41 found that males and females classified with BMI425 kg m À2 and with low fitness had a greater likelihood of being classified as hypertensive compared to individuals of the same body size but with moderate or high fitness.…”
Section: Discussionmentioning
confidence: 86%
“…17 The results of previous studies have suggested that the relationship between aerobic fitness and CVD risk factors in youth is mediated by body fatness. 15,16 Furthermore, Boreham et al 18 concluded that the cardiovascular health of children may be better associated with fatness than aerobic fitness. To our knowledge, no reports have considered the interactions between aerobic fitness and BMI among adolescents, and their influence on CVD risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Given that insulin resistance could be a predictor of obesity and cardiovascular risk factors [34], the findings of these studies could explain some of our results and suggest that maybe the insulin resistance could be the mediator link between CRF, obesity and clustered risk factors. If we assume that fatness is the main mediator of the relationship between clustered risk factors and CRF [35] we do not take in consideration the fact that insulin resistance could be the link behind this relation. Further, insulin sensitivity is mainly related to the muscle tissue, because a great portion of the carbohydrate is stored or burned in the muscle [36].…”
Section: Discussionmentioning
confidence: 99%